ABC News Libya Poll, March 1986 ([Verlag nicht ermittelbar], 1988)
This survey was conducted after fighting broke out between Libyan and United States forces in the Bay of Sidra. Respondents were asked if they approve of Reagan's handling of the situation, if they believe that the United States has a right to have vessels in the Bay of Sidra, if the United States should be holding military exercises there, and whether or not they think that the military actions have been too tough. In addition, respondents were asked questions concerning the sending of military aid to Honduras and to the Nicaraguan rebels.